2016
DOI: 10.1016/s1473-3099(15)00362-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of ChAd3-EBO-Z Ebola virus vaccine in Malian and US adults, and boosting of Malian adults with MVA-BN-Filo: a phase 1, single-blind, randomised trial, a phase 1b, open-label and double-blind, dose-escalation trial, and a nested, randomised, double-blind, placebo-controlled trial

Abstract: SummaryBackgroundThe 2014 west African Zaire Ebola virus epidemic prompted worldwide partners to accelerate clinical development of replication-defective chimpanzee adenovirus 3 vector vaccine expressing Zaire Ebola virus glycoprotein (ChAd3-EBO-Z). We aimed to investigate the safety, tolerability, and immunogenicity of ChAd3-EBO-Z in Malian and US adults, and assess the effect of boosting of Malians with modified vaccinia Ankara expressing Zaire Ebola virus glycoprotein and other filovirus antigens (MVA-BN-Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(161 citation statements)
references
References 20 publications
5
150
0
6
Order By: Relevance
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Соглас-но полученным результатам, количество антител у добровольцев к гликопротеину штамма Заир вируса Эбола находилось на уровне, обеспечи-вающем поствакцинальный защитный иммуни-тет у нечеловекоподобных приматов по данным ранних предклинических исследований [13]. Со-гласно предварительным данным, вакцина VRC-EBOADC076-00-VP (cAd3-EBOZ) также является безопасной и иммуногенной, а ее комбинация с вакциной MVA-BN-Filo на основе модифици-рованного вируса осповакцины, содержащего антигены гликопротеинов (GP) штамма Таиланд, Заир, Судан и вируса Марбурга, может быть ис-пользована для формирования более длительно-го иммунного ответа [32].…”
Section: вакцины на основе ад-векторовunclassified
“…38 Since studies in NHPs had shown that immunogenicity and duration of high-level protection against challenge could be extended by administering a dose of MVA-BN Filo as a booster. 34 Another study of ChAd3-EBO-Z with MVA-BN Filo among Malian and US adults began in late November 2014 39 (ClinicalTrials.gov NCT02231866 and NCT02267109, respectively) ( Table 2). It was the first time that ChAd3-EBO-Z was administered to Africans participants.…”
Section: Non-replicative Vector-based Ebola Vaccinesmentioning
confidence: 99%
“…In November 2015, the results from one of 6 previous clinical trials (ClinicalTrials.gov NCT02267109) showed a well tolerance and strong immunogenicity of prime-boost regimen. 39 Since administration with MVA-vectored vaccine is capable of extending the duration of protection, more and more studies using MVA-vectored vaccines as booster are been conducted now.…”
Section: Mva-vectored Vaccinesmentioning
confidence: 99%